2016
DOI: 10.1111/jpc.13157
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing autism: Contemporaneous surveys of parent needs and paediatric practice

Abstract: Parents want more information than can be conveyed in a single diagnostic consultation. Developing a tailored 'autism action plan' with written materials could improve parents' understanding of and satisfaction with children's autism diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 18 publications
1
44
0
6
Order By: Relevance
“…However, the engagement between clinicians and schools can be improved. For example, Australian research found that, although 89% of parents wanted their paediatrician to help to inform their child's school after an ASD diagnosis, only 19% received this support . Future research will have an important role to play in facilitating this, for example, by evaluating different approaches to fostering such engagement.…”
Section: Discussionmentioning
confidence: 99%
“…However, the engagement between clinicians and schools can be improved. For example, Australian research found that, although 89% of parents wanted their paediatrician to help to inform their child's school after an ASD diagnosis, only 19% received this support . Future research will have an important role to play in facilitating this, for example, by evaluating different approaches to fostering such engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Most parents of young children in this study felt that information should be provided immediately after the diagnosis, including information on organizations and services and on what to expect with ASD. In a more recent Australian survey of 404 parents and 53 pediatricians, parents rated the following as most important information to receive at diagnosis: how to find allied health professionals with ASD experience, what the diagnosis meant, how it was made, and what the prognosis was 196. Crucially, pediatricians reported giving more information on allied health professionals, prognosis, and funding than parents perceived receiving.…”
Section: Family Preferences For Asd Diagnostic Assessmentmentioning
confidence: 99%
“…The diagnosis of ASD is primarily based on behavioral evaluation (Hennel et al 2016), as potential reliable biomarkers are still in an investigative phase (Varcin and Nelson, 2016). In recent years, morphological changes in the brain (e.g.…”
Section: Introductionmentioning
confidence: 99%